The mutual correlation of CIC and CCEO in light of their autonomous operation - NOWICKA, URSZULA (Prawo Kanoniczne, 2012)
After promulgation of Code of Canons of Oriental Churches in 1990, we encounter in canonical doctrine the view that the CCEO is lex specialis in regards to the CIC, or that the Eastern Code obliges the Latin faithful as the later norm of the same Supreme Lawgiver. On the other hand according to the CCEO Canon 1 „The canons of this Code affect all and solely the Eastern Catholic Churches, unless, with regard to relations with the Latin Church , it is expressly stated otherwise”. This article aims to analyze the relationship between the two Codes of the Church: CCEO canons, which apply to the Latin faithful (direct and indirect interrelation) and possible application of the CCEO norms as ancillary source for the interpretation of the CIC.